O sistema de formação, aplicação e superação dos precedentes vinculantes - Araújo Júnior, Pedro Dias de (2017)
The present master thesis has its start point on Nicklas Luhmann's system theory and political science in David Easton to demonstrate that the legal system interacts with society through structural couplings, creating binding precedents through existing normative consolidation or, alternatively, from current legal system. One of the key points of the thesis is the participation of the amicus curiae as a legitimizing element of the binding precedents policy. Although they interpret the law in very open interpretation, we defend the thesis that this interpretation can not have the breadth defendend by Peter Häberle in the sense of being greatly enlarged, but the interpretations outside the legal system are realized through codes because a fundamental characteristic of any sound social system – including law system - is open cognitiveness and closed operability according to Luhmann's theory, creating rules and these same rules return to the environment. In the formation of the precedent, we analyzed the participation of the amicus curiae as an element of cognitive openness. In its application, we understand that the integrity of the system should not be understood only in its Dworkian principle theory, defended by Lenio Streck, but rather that it should be understood as a system, in the light of Luhmann's theory. The preservation of the internal operability of the subsystem of binding precedents is one of the means to avoiding systemic corruption - this defies the integrity of any kind of system. With regard to the application of the precedents, there is a need for a more detailed study of the ratio decidendi and the obiter dictum, in order to correct the innumerable imperfetcions of judicial decisions in Brazil, especially those coming from the Federal Supreme Court. When studying the precedents, it is discovered that frozen view of jurisprudence is more typical of the English system than the American system, which makes predict that the Brazilian system will also be more flexible than the two systems under study. In the Constitutional Court, we analyze the main arguments for and against the constitutionality of the binding precedents system and we conclude by its constitutionality. Finally, after the extensive study, it competed to frame the binding precedent - and not the jurisprudence - as a formal source of Brazilian law.